The application of orthopedic equipment in the form of orthoses in children suffering from cerebral palsy - Stecko, Monika; Wawryków, Agata; Korabiusz, Katarzyna; Harasimowicz, Joanna; Fabian-Danielewska, Anna; Piątek, Patrycja; Żukowska, Magdalena; Kordek, Agnieszka (Journal of Education, Health and Sport, 2019)
Cerebral palsy is a broad term, including various, changing with age movement and postural disorders of cerebral origin [1]. Gait of children suffering from cerebral palsy is characterized by changeability. Observed gait abnormalities are caused by incorrect steering of movements of a child and they are the effects of brain damage and compensation mechanisms. The orthoses should be applied in children suffering from cerebral palsy to protect against deformations of lower limbs. An orthosis prevents the occurrence of articular contractures, probably as a result of inhibition of biomechanical changes in periarticular collagen caused by immobilization [9,10]. Selecting an appropriate orthosis is a key element of the process of treatment of diseases of musculoskeletal system. Orthosis should always be selected individually, depending on the needs and capabilities of a patient. The following orthoses can be distinguished: ankle joint orthoses, dynamic foot orthosis and complex orthoses stabilizing ankle joint, knee joint and hip joint. Selecting an appropriate orthopedic equipment is a very important aspect in complex rehabilitation of children suffering from cerebral palsy.